Selection and Characteristics of Antimicrobial Starter Mix of Non-Probiotic and Probiotic in ‘Kecipir’ Yogurt - Rekapermana W.S.; Cahyadi Cahyadi (Jurnal Agrosci, 2025)
Background. Now, the role of functional food has become more important in maintaining and controlling public health. Yogurt can be an alternative, as it is familiar, well-liked, and has been reported by many for its functional properties. Aims. The development of ‘kecipir’ed ‘kecipir’s (Psophacarpus tetragonolobus L.) into food products is still relatively rare, even though it has great potential because it contains high nutrients and several bioactive components. The manufacture of ‘kecipir’s into yogurt, especially using lactic acid (BAL) bacterial starters, is a mixture of nonprobiotic yogurt (SY) starter and probiotic starter (SP), which is expected to improve its functional properties. One of the essential functional properties of yogurt is its antimicrobial properties. Methods. This research was made in two stages. Phase I aimed to identify the best antimicrobial properties of the 7 BALs (2 SY and 5 BAL SP) against E. coli and Staphylococcus aureus. The antimicrobial activity test employed the agar diffusion method, which is measured by the diameter of the clear zone of inhibition around the sound hole in the agar medium. Phase II aims to determine the optimal combination of a 4% starter mixture (SY+SP) that produces the best antimicrobial and organoleptic properties in cheesecake yogurt. Result. Phase I research produced four best BAL starters, namely two SY (BAL 1 Lactobacillus bulgaricus FNCC 0041 UGM and BAL 2 Streptococcus thermophillus ITB), as well as two SP (BAL 5 Lactobacillus acidophillus UNPAD and BAL 7 Bifidobacterium spp UNPAD). Phase II research obtained results that the antimicrobial properties were significantly different at the level of 5%, from the highest, namely SY4–SP0 starters at level a, SY1–SP3 starters at levels a, b, and combinations of SY3–SP1, SY2–SP2, and SY0–SP4 at level b. Organoleptically (hedonic), the combination of SY1–SP3 was the highest preferred by the panelists. Conclusion. So the best mixed starter in this study is SY1–SP3, which comprises 1% of the SY starter mixture and 3% of the SP starter mixture